Design-oriented strength of mechanical joints in composite laminate structures and reliability-based design factor. (15th November 2015) - Nakayama, Masahiro; Uda, Nobuhide; Ono, Kousei; Takeda, Shin-ichi; Morimoto, Tetsuya
Abstract: Mechanical joints may act as bottlenecks in the design process of composite structures. Fitting factors need to be multiplied with the applied load condition to assure reliability. For more efficient design, this paper proposes a brand-new design-oriented strength: knee point strength for the mechanical joints in composite laminates. The knee point strength is derived from the stiffness change rate for the bearing stress–strain behavior in a bearing test. The strength can be correlated with the internal bearing damage; this is verified by micrography about the bearing test specimen and finite element analysis. The probabilistic design and analysis method was applied to acquire the reliability-based fitting factor. An approach combining finite element damage analysis and a stochastic technique was adopted to analyze the probabilistic properties for the design-oriented strength of the bolted joints in CFRP laminates. The probabilistic and deterministic designs were compared and discussed. Then a proper value of the fitting factor was proposed.